ASSOCIATION OF NET PTERYGIUM TISSUE MASS (DRY-WEIGHT) IN DETERMINING CHANGES IN OCULOVISUAL FUNCTIONS AND ANTERIOR CORNEAL CURVATURE RELA-TIVE TO PTERYGIUM TYPES - CHE ROSLI, NOOR SYAHIRA; HILMI, MOHD RADZI; MOHD KAMAL, KHAIRIDZAN; MD MUSTAFA, MD MUZIMAN SYAH (International Journal of Allied Health Sciences, 2020)
Introduction: Dryweight in pterygium is more towards the fleshy appearance of the fibrous tissue. Aim: The goal of this study was to determine the predictive ability of net pterygium tissue mass (dryweight) on predicting changes in anterior corneal curvature and oculovisual functions relative to pterygium types. Methodology: A total of 93 primary pterygium patients who visited an ophthalmology clinic were selected as participants. The net pterygium tissue mass were obtained via freeze dry method subsequent to pterygium excision using fibrin glue adhesive method. Best corrected visual acuity (BCVA) and contrast sensitivity function (CSF) were measured by using M&S Smart System II as measurement for oculovisual function, while the changes of anterior corneal curvature was measured using corneal topography. Results: The mean and standard deviation for BCVA, CSF and SimK were 0.44 ± 0.30 LogMAR, 24.28 ± 17.66 % and 4.64 ± 4.18 D respectively. This study found that the predictive ability of pterygium dryweight with BCVA were strong in Type I and Type III while moderate in Type II with 13.10% (R2 = 0.131, p < 0.05) in Type I. Slight increase trend were noted in both Type II with 53% (R2 = 0.530, p < 0.05) and Type III, with 21.60% (R2 = 0.216, p < 0.05). For CSF, the predictive ability of pterygium dryweight were strong in all types with Type I, Type II and III reported 21.6% (R2 = 0.216, p < 0.05), 31.8% (R2 = 0.318, p < 0.05), 28.9% (R2 = 0.289, p < 0.05) respectively. The predictive ability of pterygium dryweight for SimK were strong in all types with contribution of 44.7% (R2 = 0.447, p < 0.05), 47.7% (R2 = 0.477, p < 0.05), 39.1% (R2 = 0.391, p < 0.05) respectively. Conclusion: Net pterygium tissue mass (dryweight) is a strong factor in predicting changes of oculovisual functions and anterior corneal curvature in relation to pterygium types.